F2-Isoprostanes as Novel Biomarkers for Type 2 Diabetes: a Review - Kaviarasan, Subramanian; Muniandy, Sekaran; Qvist, Rajes; Ismail, Ikram Shah (The Society for Free Radical Research Japan, 2009)
Oxidative stress (OS) has been implicated as one of the major underlying mechanisms behind many acute and chronic diseases. However, the measurement of free radicals or their end products is complicated. Isoprostanes, derived from the non-enzymatic peroxidation of arachidonic acid are now considered to be reliable biomarkers of oxidant stress in the human body. Isoprostanes are involved in many of the human diseases such as type 2 diabetes. In type 2 diabetes elevated levels of F-2-Isoprostanes (F-2-IsoPs) have been observed. The measurement of bioactive F-2-IsoPs levels offers a unique noninvasive analytical tool to study the role of free radicals in physiology, oxidative stress-related diseases, and acute or chronic inflammatory conditions. Measurement of oxidative stress by various other methods lacks specificity and sensitivity. This review aims to shed light on the implemention of F-2-IsoPs measurement as a gold-standard biomarker of oxidative stress in type 2 diabetics.